Analisis Kesalahan Sintaksis Bahasa Indonesia Dalam Karangan Deskripsi Siswa Kelas Tinggi yang Berbahasa Ibu Bahasa Batak - Juliana, Eva; Nasution, Afrilliani; Apleni, Rima; Syahriani, Rica (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
One of the aims of this research is to (1) explain the types of syntactic errors that occur in single sentences in descriptive essays written by students who meet high academic standards, and (2) explain the types of syntactic errors that occur in compound sentences written by students. that meets high academic standards. This research is qualitative research. This research involved high class students whose mother tongue was Batak. The data used in this research are single and compound Indonesian sentences that violate language at the syntactic level in their free essays. The results showed that 13 out of 18 students, or 72 percent of the students, made mistakes in their essays. The results showed that high class students who spoke Batak as their mother tongue made syntactic errors in one single sentence. These syntactic errors are (1) sentences that are ungrammatical, (2) sentences that are not coherent, (3) sentences that are ineffective, and (4) sentences that are influenced by the Batak language. Syntactic errors in equivalent compound sentences are (1) equivalent compound sentences that are ungrammatical, (2) equivalent compound sentences that are not coherent, and (3)equivalent compound sentences that are ineffective, and (4) equivalent compound sentences. Keywords: syntax errors, Indonesian essays, Batak mother tongue.